A pleiotropic ATM variant (rs1800057 C>G) is associated with risk of multiple cancers. (13th October 2021) - Qian, Danwen; Liu, Hongliang; Zhao, Lingling; Luo, Sheng; Walsh, Kyle M; Huang, Jiaoti; Li, Chuan-yuan; Wei, Qingyi
Abstract: ATM (ataxia–telangiectasia mutated) is an important cell-cycle checkpoint kinase required for cellular response to DNA damage. Activated by DNA double strand breaks, ATM regulates the activities of many downstream proteins involved in various carcinogenic events. Therefore, ATM or its genetic variants may have a pleiotropic effect on cancer development. We conducted a pleiotropic analysis to evaluate associations between genetic variants of ATM and risk of multiple cancers. With genotyping data extracted from previously published genome-wide association studies of various cancers, we performed multivariate logistic regression analysis, followed by a meta-analysis for each cancer site, to identify cancer risk-associated single-nucleotide polymorphisms (SNPs). In the ASSET two-sided analysis, we found that two ATM SNPs were significantly associated with risk of multiple cancers. One tagging SNP (rs1800057 C>G) was associated with risk of multiple cancers (two-sided P = 5.27 × 10 −7 ). Because ATM rs1800057 is a missense variant, we also explored the intermediate phenotypes through which this variant may confer risk of multiple cancers and identified a possible immune-mediated effect of this variant. Our findings indicate that genetic variants of ATM may have a pleiotropic effect on cancer risk and thus provide an important insight into common mechanisms of carcinogenesis. Abstract : A pleiotropic analysis was conducted to evaluate associations between genetic variants of ATM and risk of multiple cancers, including cancers of the breast, lung, prostate, pancreas, head and neck cancer as well as melanoma and glioma. In the ASSET two-sided analysis, we found that two ATM SNPs were significantly associated with risk of multiple cancers. One tagging SNP (rs1800057 C>G) was associated with risk of multiple cancers (two-sided P  = 5.27 × 10 −7 ). We explored the intermediate phenotypes through which the missense variant ATM rs1800057 may confer risk of multiple cancers and identified a possible immune-mediated effect of this variant.